Bidirectional Propulsion of Arc‐Shaped Microswimmers Driven by Precessing Magnetic Fields. (27th May 2020) - Mohanty, Sumit; Jin, Qianru; Furtado, Guilherme Phillips; Ghosh, Arijit; Pahapale, Gayatri; Khalil, Islam S. M.; Gracias, David H.; Misra, Sarthak
Abstract : The development of magnetically powered microswimmers that mimic the swimming mechanisms of microorganisms is important for lab‐on‐a‐chip devices, robotics, and next‐generation minimally invasive surgical interventions. Governed by their design, most previously described untethered swimmers can be maneuvered only by varying the direction of applied rotational magnetic fields. This constraint makes even state‐of‐the‐art swimmers incapable of reversing their direction of motion without a prior change in the direction of field rotation, which limits their autonomy and ability to adapt to their environments. Also, due to constant magnetization profiles, swarms of magnetic swimmers respond in the same manner, which limits multiagent control only to parallel formations. Herein, a new class of microswimmers are presented which are capable of reversing their direction of swimming without requiring a reversal in direction of field rotation. These swimmers exploit heterogeneity in their design and composition to exhibit reversible bidirectional motion determined by the field precession angle. Thus, the precession angle is used as an independent control input for bidirectional swimming. Design variability is explored in the systematic study of two swimmer designs with different constructions. Two different precession angles are observed for motion reversal, which is exploited to demonstrate independent control of the two swimmer designs. Abstract : Arc‐shaped microswimmers that are capable of reversible motion triggered by changing the precession angle of applied magnetic actuation are presented. The geometrical constituents of the swimmers assume different spatial configurations, driven by their precession‐induced alignment, thereby causing their motion reversal. A systematic study of two structural designs of swimmers enables their independent actuation premised upon differences in their precession‐speed characteristics.